2000
DOI: 10.1002/(sici)1521-4141(200004)30:4<1145::aid-immu1145>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of thymic function by measuring T cell receptor excision circles within peripheral blood and lymphoid tissues in monkeys

Abstract: The thymus is the primary organ responsible for the production of mature TCR α / β T cells. Quantification of a DNA excision circle that is produced during TCR rearrangement, termed a signal joint TCR rearrangement excision circle (sjTREC) can be used as a measure of thymic function. Here sjTREC measurement has been applied to two monkey species used as animal models of human disease, rhesus macaques (Asian origin) and sooty mangabeys (African origin). Initial PCR analysis determined that the TCR δRec‐ΨJα rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 29 publications
4
51
0
1
Order By: Relevance
“…TREC are stable and are not duplicated during mitosis; therefore, TREC concentration is diluted out with each cell division. This explains why thymocytes have higher TREC concentrations as compared with peripheral blood T cells (11,12), and why naive T cells have higher TREC concentrations than memory T cells (10).…”
Section: Reevaluation Of T Cell Receptor Excision Circles As a Measurmentioning
confidence: 85%
See 2 more Smart Citations
“…TREC are stable and are not duplicated during mitosis; therefore, TREC concentration is diluted out with each cell division. This explains why thymocytes have higher TREC concentrations as compared with peripheral blood T cells (11,12), and why naive T cells have higher TREC concentrations than memory T cells (10).…”
Section: Reevaluation Of T Cell Receptor Excision Circles As a Measurmentioning
confidence: 85%
“…Thus, quantification of TREC levels in different LT compartments would contribute greatly to our understanding of TREC dynamics. One study using a primate animal model observed that CD4 ϩ and CD8 ϩ T cells present in the lymph nodes contain more sjTREC than do peripheral blood T cells, suggesting that RTE can home into lymphoid tissues (11). Another study using a rat model observed that the percentages of RTE among T cell population were comparable in blood and all other LT compartments, indicating that rat RTE continuously migrate through blood and lymphoid organs as naive T cells (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TREC consist of fragments of DNA excised during rearrangement of TCR genes and hence TREC levels represent the function of the thymus. Thus, aged subjects with an atrophied thymus have a 20-fold decrease in levels of TREC compared with young subjects (22) and nonhuman primates subjected to thymectomy have a 40-fold decrease in the levels of TREC 1 year after the procedure (23,24). If the T cell compartment of recipients of cardiac transplants was restored by proliferation of residual T cells, a decrease in levels of TREC in these subjects would indicate a lack of thymic function.…”
Section: Thymic Function and Restoration Of The T Cell Compartmentmentioning
confidence: 99%
“…In the steady state normal murine adult thymus, 1.7% of the TCR high CD4 ϩ CD8 Ϫ SP (CD4SP) and 5.2% of the TCR high CD4 Ϫ CD8 ϩ SP (CD8SP) incorporate the DNA precursor bromodeoxyuridine (BrdU) within 4 h (10). In previous studies, we found that SP thymocytes that are submitted to such proliferation (also suggested in monkeys (12)) are totally mature (CD24 Ϫ , Qa-2 high ), thus being more similar to recent thymic emigrants (RTEs) and peripheral T cells than to the bulk of thymic medullary SP TCR high cells. This proliferation concerns cells that recently matured in the thymus, and therefore excludes mature T cells reentering the thymus (10).…”
Section: Quantitative and Qualitative Adjustment Of Thymic T Cell Promentioning
confidence: 93%